2019
DOI: 10.1049/iet-cvi.2018.5787
|View full text |Cite
|
Sign up to set email alerts
|

Moving vehicle tracking based on improved tracking–learning–detection algorithm

Abstract: This study addresses the tracking-learning-detection (TLD) algorithm for long-term single-target tracking of moving vehicle from video streams. The problems leading to tracking failures in existing TLD methods are discovered, and an improved TLD (ITLD) tracking algorithm is proposed which is more robust to object occlusion and illumination variation. A square root cubature Kalman filter (SRCKF) is employed in the tracker of TLD to predict the position of the object when occlusion occurs. Besides, this study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, for the use of UAV to track dynamic objects, the inertia and external disturbance generated during the flight of UAV make the object have large position changes on the adjacent frame images, and it is unable to generate motion information with certain rules to provide prediction, which will cause inaccurate object prediction position, thus losing the object. Given such problems, researchers combine image registration technology with the traditional moving object trajectory prediction method, to locate the moving object more accurately [2][3] . However, under the airborne aerial photography task with disturbance, the continuous switching method may lead to an unnecessary computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the use of UAV to track dynamic objects, the inertia and external disturbance generated during the flight of UAV make the object have large position changes on the adjacent frame images, and it is unable to generate motion information with certain rules to provide prediction, which will cause inaccurate object prediction position, thus losing the object. Given such problems, researchers combine image registration technology with the traditional moving object trajectory prediction method, to locate the moving object more accurately [2][3] . However, under the airborne aerial photography task with disturbance, the continuous switching method may lead to an unnecessary computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…As a fundamental and important problem in computer vision, object detection has been continuously investigated in the past decades. With the development of deep learning in recent years, object detection has made great progression and been widely applied in various real‐world applications, such as vehicle detection [1–4], pedestrian detection [5–9], intelligent monitoring [10–13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al used the single-target long-time algorithm to track, learn, and monitor the moving vehicle for a long time from the video stream. The problem was found that caused the tracking failure in the algorithm, and an improved tracking algorithm was proposed [6]. The overspeed of some vehicles becomes an obstacle of tracking.…”
Section: Introductionmentioning
confidence: 99%